Taxonomic challenges in freshwater fishes: a mismatch between morphology and DNA barcoding in fish of the north‐eastern part of the Congo basin. (6th August 2015) - Decru, Eva; Moelants, Tuur; De Gelas, Koen; Vreven, Emmanuel; Verheyen, Erik; Snoeks, Jos
Abstract: This study evaluates the utility of DNA barcoding to traditional morphology‐based species identifications for the fish fauna of the north‐eastern Congo basin. We compared DNA sequences (COI) of 821 samples from 206 morphologically identified species. Best match, best close match and all species barcoding analyses resulted in a rather low identification success of 87.5%, 84.5% and 64.1%, respectively. The ratio 'nearest‐neighbour distance/maximum intraspecific divergence' was lower than 1 for 26.1% of the samples, indicating possible taxonomic problems. In ten genera, belonging to six families, the number of species inferred from mtDNA data exceeded the number of species identified using morphological features; and in four cases indications of possible synonymy were detected. Finally, the DNA barcodes confirmed previously known identification problems within certain genera of the Clariidae, Cyprinidae and Mormyridae. Our results underscore the large number of taxonomic problems lingering in the taxonomy of the fish fauna of the Congo basin and illustrate why DNA barcodes will contribute to future efforts to compile a reliable taxonomic inventory of the Congo basin fish fauna. Therefore, the obtained barcodes were deposited in the reference barcode library of the Barcode of Life Initiative.